The Effectiveness of Using Direct Sunlight on the Drying Process of Salted Fish Without Formalin - Sabilah, Adina; Khairunnisa, Alda; Monalia, Monalia; Sahriani, Sisi; Putri, Widya Pratama Sri; Lubis, Yusri Amiroh; Marta, Eni (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2022)
Salted fish is one of the side dishes that are in great demand by the people of Indonesia. This study aims to analyze the effectiveness of the use of direct sunlight on the drying process of salted fish without formalin. The method used in this research is the experimental method. Where this data collection uses various types of fish to be used as salted fish and there are also some fish that are not salted. The types of fish used in this study were river fish, tilapia, singkek fish, and marine fish. The process of making this salted fish lasts 3-5 days. It depends on the type of fish used and the weather or sunlight during the drying process. The drying process of salted fish that is applied is using direct sunlight or traditionally and does not use chemicals or formalin. The results obtained during drying, fish that do not use salt easily spoil quickly and cannot last long. The smell of unsalted fish is more pungent and the color of the fish also changes. While the fish that is given salt does not smell bad, the color of the fish also does not change.